A comparison study between Magniview and high definition white light endoscopy in detecting villous atrophy and coeliac disease: A single centre pilot study. Issue 9 (September 2018) - Raju, Suneil A.; White, William L.; Lau, Michelle S.; Mooney, Peter D.; Rees, Michael A.; Burden, Mitchell; Ciacci, Carolina; Sanders, David S.
Abstract: Background and aims: Coeliac disease may be missed at gastroscopy. We aimed to assess the sensitivity of Pentax optical zoom technology endoscopes in detecting duodenal villous atrophy and the ease of image interpretation by non-coeliac specialists. Method: All patients attending for a gastroscopy were assessed for endoscopic villous atrophy in part one and two of the duodenum with high definition white light endoscopy and magnification endoscopy. Endoscopic findings of the duodenum were compared to histology as the reference standard. A short training video of varying degrees of villous atrophy seen by magnification endoscopy was used to train individuals. They were then assessed for the ability to differentiate between normal duodenum and villous atrophy. Results: Two hundred and fifty patients were prospectively recruited (145 females, 58%; age range 16–84, median age 50.5). Ninety-six patients had villous atrophy on histology (38.4%) 154 were controls. Magnification endoscopy had a higher sensitivity in detecting villous atrophy compared to high definition white light endoscopy (86.4% versus 78.4%, p = .0005). 9/10 individuals undertaking magnification endoscopy training correctly identified all cases of villous atrophy. Conclusion: Magnification endoscopy has superior diagnostic sensitivity in detecting villous atrophy compared to high definition white light endoscopy and the potential to be easily adopted by all endoscopists.